POLITICAL RISKS AND INVESTMENT: A CASE STUDY OF PAKISTAN (2012-2022) - Rasib Lal; Muhammad Waseem Yousaf; Prof. Dr. Asia Saif Alvi (International Journal of Contemporary Issues in Social Sciences, 2024)
This research article explores the link between political risks and patterns of foreign direct investment in Pakistan from the period of 2012-2023. By utilizing both qualitative and quantitative research methods, the study evaluates the level of disturbance caused by political instability, policy inconsistency, outdated infrastructure, bureaucratic hurdles, inflexible tax and tariff paradigms, corruption and other political risks to the flow of domestic and foreign investments in Pakistan. Findings of research suggest that in each period, Pakistan witnessed a decline inflow of investment, although, in some years, a minor increase occurred but it made a slight difference in overall investment. The study endorses the fact that political stability, a conducive atmosphere, flexible policy and regulations help to boost the confidence of investors and it leads to more flow of investment in the country. The smooth flow of investment requires targeted reforms to mitigate the political risks and stimulate sustainable economic growth in Pakistan.